THE INCIDENCE OF VARICELLA IN CHILDREN AT HIGH RISK: EPIDEMIOLOGICAL AND CLINICAL FEATURES, THE COST OF THE DISEASE AND POTENTIAL COST-EFFECTIVENESS OF VACCINATION - O.Ya. Deineko; T.G. Avdeeva; N.V. Sulimova; D.N. Trashchenkova (Педиатрическая фармакология, 2011)
Outbreaks of varicella in children’s groups raises a number of public health and economic problems. The aim of this study was to investigate the epidemiological and clinical features of the development and course of chickenpox in children of different ages from high-risk groups, as well as to analyze the estimated cost of the disease and the potential cost-effectiveness of vaccination. The analysis of the incidence of varicella and its complications in children raised in specialized children’s home (in 2009) and treated at the social rehabilitation center for minors in Smolensk (in 2010). Infections and hospitalizations cases were accounted on the basis of the stories of children medical histories (f. 112, f. 26). We performed the calculation of the illness cost and possible cost-effectiveness of prevention of infection by a double Varilriks vaccination. It is shown that the incidence of chickenpox in closed team (orphanage)  was 40,8% (64 out of 157 children previously not suffered from chickenpox), in an open team (rehabilitation center) — 71,4% (30 out of 42 children). All sick children from the orphanage and 25 of the 30 infected from the rehabilitation center were hospitalized. Cost of illness (direct medical costs associated with inpatient and ambulatory settings) was 939 821 and 633 986 rub., respectively,  which was 3,0 (314 000 rub.) and 7,5 times (84 000 rub.) more expensive than vaccinations. Thus, the savings could amount to 625 821 (-66,6%) and 549 986 rubles. (-86,8%), respectively. Key words: children, chickenpox, morbidity, hospitalization, complications, cost of illness, vaccination. (Pediatric pharmacology. — 2011; 8 (6): 12–16).